FENOMENA INVESTASI ILEGAL DI INDONESIA DALAM TINJAUAN PERSPEKTIF PSIKOLOGIS - Rahma Suryani; Agung Perdana Putra; Ahmaddin Ahmad Tohar; Khairil Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of illegal investment in Indonesia is increasingly rampant along with the development of financial technology and low financial literacy of the public. This study aims to examine the behavior of illegal investment from a psychological perspective by highlighting the psychological impact it causes. The research method used is library research through the analysis of various sources such as journals, articles, and official reports. The results of the study show that illegal investment behavior is not only triggered by a lack of financial and legal knowledge, but also by psychological factors such as social influence and trust in public figures (celebrity endorsement effect), cognitive bias (optimism bias and overconfidence bias), and the phenomenon of Fear of Missing Out (FoMO). These factors encourage individuals to make investment decisions emotionally without rational consideration of risk. The impact is not only in the form of financial losses, but also psychological trauma, loss of social trust, and decreased public participation in formal financial institutions. This research emphasizes the importance of increasing financial literacy and psychological awareness of the community as a preventive effort against illegal investment practices in Indonesia.